Optimizacija procesnih parametrov pri kontinuiranem ulivanju jekla v železarni ACRONI Jesenice - Filipič, Bogdan (Kovine zlitine tehnologije, 1997)
The paper presents an evolutionary computation approach to process parameter optimization in continuous casting of steel. Physical background of six empirical metallurgical criteria of slab cooling is introduced. The problem of finding optimal parameter values is stated as a minimization problem based on the analytical form of the cooling criteria and on computed temperature field of the slab. To solve the optimization problem, a genetic algorithm is employed. The algorithm explores process parameter settings heuristically by applying the principles of biological evolution. Parameter settings are evaluated through numerical simulation of the casting process. The optimization procedure is shown along with the results obtained for continuous casting of stainless steel AISI 304 with slab dimensions 1,06 m x 0,2 m.
Keywords: kontinuirano litje; železarne; Jesenice; optimiranje litja; parametri optimiranja; algoritmi genetski; livarstvo; optimiranje; algoritmi